Os discursos que entrecruzam a sala de aula de língua inglesa: um olhar sobre o livro didático - SIQUEIRA, Michele (2009)
This study is an investigation of the discourses which cross the English teaching classroom, focusing, more specifically, on those which enter the classroom via textbooks. Thus, the object of this research are the texts of the reading sessions of a collection of English textbooks constituted of four books designated to the second phase of elementary school in Goiás. The aim of this analysis is to identify the themes, genres and discourses brought on these texts and the observation of their contribution to reach one of the main goals traced by the foreign language PCN, that is, the discursive engagement on the net of practices in which they take part. The text analysis and the theoretical basis of this work are founded on the theoretical and methodological principles of Critical Discourse Analysis based on the studies of Norman Fairclough (1999, 2001, 2001a, 2001b, 2003, 2006). The selection of the textbooks from which the texts analyzed were taken was based on the collections which were mostly adopted by the English teachers in Goiânia. By the observation of the discourses and the analysis of the themes and genres of the texts it could be noticed that, when certain social spheres and view points are privileged, the Besides, it demonstrates the predominance of the study of texts with the only aim of teaching the structures of the English language. Thus, it could be noticed that textbook editors should be concerned with selecting textbooks which reflect the discourses existent inside and outside the classroom, in favor of an education for freedom